Towards the bioproduction of methyl methacrylate: solving the problem of product toxicity - Disley, Zoe B.C. (2018)
Methyl methacrylate (MMA) and its derivatives are currently produced using methods which rely on crude oil resources and natural gas as feedstocks. A novel and sustainable route to the precursor methacrylic acid (MAA), has recently been developed. This method involves the production of MAA from renewable feedstocks via microbial fermentation. Unfortunately, the toxicity of MAA is a significant issue, inhibiting the growth of potential host biocatalysts at concentrations as low as 10mM. This ultimately limits production titres and reduces the economic viability of the process. Therefore, in situ product removal (ISPR) via liquid-liquid extraction has been investigated in order to reduce the concentration of MAA in the aqueous phase, preventing inhibition of the biocatalyst during its production. Twenty-two water-immiscible organic solvents were tested for biocompatibility with Escherichia coli MG1655 and Saccharomyces cerevisiae DSM70449, the majority of which were toxic towards both organisms. Surprisingly, E. coli demonstrated a significantly higher tolerance towards the solvents, particularly when grown in minimal medium. Unfortunately, the biocompatible solvents demonstrated extremely poor extraction efficiencies of between 9 – 50 % MAA, from aqueous systems. Ionic liquids (ILs) were therefore investigated as potential replacement solvents for the ISPR of MAA. Twenty-two ILs were synthesised and tested for biocompatibility with E. coli and S. cerevisiae. Seventeen biocompatible ILs were identified and their physicochemical properties and extraction capabilities were evaluated. The ILs demonstrated extraction efficiencies superior to those of traditional organic solvents, extracting up to 93 % MAA from aqueous systems. Alternatively, the direct bioproduction of alkyl methacrylate esters offers the added benefit of phase separation above a critical concentration, removing the need for an extraction solvent, and therefore their toxicity was assessed. However, the esters were found to have a higher toxicity than MAA towards E. coli and S. cerevisiae. Unexpectedly, an n-butyl methacrylate (BMA) tolerant E. coli mutant was discovered during toxicity measurements. Five BMA resistant strains were isolated and upon whole genome sequence analysis, mutations were found in three genes, soxR, acrR and ybcO. An improved BMA tolerance was found in the mutants containing both the soxR and acrR mutations. These findings offer the potential for the development of these strains to create a sustainable route to BMA.